PENGARUH DIFERENSIASI PRODUK, WORD OF MOUTH DAN BRAND AWARENESS TERHADAP KEPUTUSAN PEMBELIAN (Studi Pada CV. Eka Karunia Motor Lamongan): (Studi pada CV. Eka Karunia Motor Lamongan) - Ilham Ramadhani, Awaliansyah; Shofia Maulida, Indira; Susanti, Ike; Sutinem (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2024)
This study aims to analyze and test the effect of product differentiation, word of mouth and brand awareness on purchasing decisions for Honda motorbikes at CV. Eka Karunia Motor Lamongan. This research uses quantitative methods. The population in this study were consumers of CV. Eka Karunia Motor. The sampling method used in this study was purposive sampling of 100 respondents. The data analysis method used in this study is multiple linear regression analysis, with the help of SPSS version 23. The results of this study indicate that the variables of product differentiation, word of mouth and brand awareness partially have a positive and significant effect on purchasing decisions. And the variables of product differentiation, word of mouth and brand awareness simultaneously have a positive and significant effect on purchasing decisions. And the product differentiation variable has the most dominant effect on purchasing decisions for Honda motorbikes at CV. Eka Karunia Motor Lamongan.